Evaluation of Flooding in Sg Gita Catchment, Kuching - Mah, D.Y.S.; Hii, C.P.; Ong, C.Y.; Pui, Y. (JASPE, 2017)
This paper outlines a methodology of flow routing with inclusion of downstream river water level applied to a Sg Gita urbanized catchment beside Sg Sarawak in Kuching city, Sarawak, Malaysia. Evaluations are done by demonstrating the modelling of flooding scenarios using InfoWorks River Simulation (RS) that stresses on different aspects specific to Sg Gita’s conditions, namely (1) impacts of high and low river water levels, (2) solely urban flooding and (3) the combination of the two. The outcomes indicate that the dynamics of downstream river water level influences the performance of the urban drainage that flowed into the river. Backwater is overriding the flows of urban drains. Therefore, the mentioned methodology is found superior than conventional methodology with only flow routing to represent the flow mechanism of urban catchment bounded by a downstream river.